Motivational Factors Influencing Female Students’ English Language Learning at Bachelor’s Level in Nepal - Adhikari, Bala Ram (BMC Research Journal, 2026)
The present study, entitled Motivational Factors Influencing Female Students’ English Language Learning at the Bachelor’s Level in Nepal, attempts to explore the motivational dimensions shaping female students’ engagement with English language learning. To achieve this aim, five students enrolled in B.Ed., B.B.S., and B.A. programs at Bhairahawa Multiple Campus in Rupandehi district were selected through non-random sampling procedures. Data were collected using in-depth interviews guided by a semi-structured interview protocol, allowing participants to articulate their lived experiences of learning English during their undergraduate studies. Thematic analysis of the coded data revealed that motivation plays a pivotal role in sustaining students’ learning trajectories. The emergent themes highlighted five major sources of motivation: teachers as inspirational figures, text as a motivating resource, teaching methods as influential practices, teaching materials as supportive tools, and tests as evaluative drivers of effort and persistence. These findings underscore the multifaceted nature of motivation in English language learning and provide insights into how pedagogical practices and academic contexts shape female students’ learning experiences at the Bachelor’s level in Nepal.